2005
DOI: 10.1254/jphs.fp0040512
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Properties of a Prior Oral Loading of Amiodarone in In Vivo Canine Coronary Ligation/Reperfusion-Induced Arrhythmia Model: Comparison With Other Class III Antiarrhythmic Drugs

Abstract: Abstract. Amiodarone, which is generally classified as class III antiarrhythmic drug in the Vaughan Williams classification, is widely used for the treatments of refractory arrhythmias. However, we previously reported that intravenous infusion of amiodarone (6.67 mg / kg per hour) did not suppress arrhythmias induced by coronary ligation / reperfusion in dogs. In this study, we examined effects of a prior oral loading of amiodarone on arrhythmias induced by coronary ligation / reperfusion. Sixteen female beagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In vitro experiments, using breast and prostate cancer cell lines, demonstrate that bisphosphonates promote apoptosis and block cell proliferation [ 139 , 140 ]. In addition, studies using OC cell lines and animal models have shown that bisphosphonates have an anti-proliferative and pro-apoptotic activity through the inhibition of cell proliferation and angiogenesis, induction of apoptosis, and activation of immune cells [ 141 , 142 , 143 , 144 , 145 , 146 ]. A recent study demonstrated that bisphosphonates inhibit OC cell lines proliferation in a concentration-dependent manner in vitro and potentiate a delay in tumour formation and a decrease in tumour cell proliferation in transgenic OC mouse models ( Figure 1 ) [ 147 ].…”
Section: Drug Repurposing For Ovarian Cancer Therapymentioning
confidence: 99%
“…In vitro experiments, using breast and prostate cancer cell lines, demonstrate that bisphosphonates promote apoptosis and block cell proliferation [ 139 , 140 ]. In addition, studies using OC cell lines and animal models have shown that bisphosphonates have an anti-proliferative and pro-apoptotic activity through the inhibition of cell proliferation and angiogenesis, induction of apoptosis, and activation of immune cells [ 141 , 142 , 143 , 144 , 145 , 146 ]. A recent study demonstrated that bisphosphonates inhibit OC cell lines proliferation in a concentration-dependent manner in vitro and potentiate a delay in tumour formation and a decrease in tumour cell proliferation in transgenic OC mouse models ( Figure 1 ) [ 147 ].…”
Section: Drug Repurposing For Ovarian Cancer Therapymentioning
confidence: 99%
“…After stabilization following the surgical procedures, a drug was given by an intravenous bolus or by an infusion and then coronary occlusion followed by reperfusion was performed. In some experiments, chronic oral administration of drugs for days or weeks before the experiment was performed (87,88). The occurrence of PVC or VF was monitored by continuous ECG recordings.…”
Section: -5-2 Methodsmentioning
confidence: 99%
“…As stated above, some K + -channel blockers were effective, but others, amiodarone (50,87), dofetilide (48), KCB-328 (49), sematilide (47) and, d-sotalol (84), were not effective in halothane-anesthetized dogs; and dofetilide (48) and sematilide (47) were not effective in pentobarbital-anesthetized dogs (6). Also in the halothane anesthetized low heart rate open chest dogs, some of the K + -channel blockers, amiodarone (50), dofetilide (48), E-4031 (46), KCB-328 (49), nifekalant (84), and sematilide (47), showed a proarrhythmic effect by spontaneously inducing PVC and VT before applying coronary occlusion, but these arrhythmias before applying coronary occlusion were not observed in high heart rate pentobarbital-anesthetized dogs by dofetilide (48) (88), administration in rat models.…”
Section: -5-4 Ineffective and Proarrhythmic Drugsmentioning
confidence: 99%
“…Additionally, depending on their respective binding/unbinding time constants, drugs may or may not interact with the conduction velocity and modify the duration of the repolarization phase differently (e.g. class IA, class IB, class IC in the Vaughan-Williams classification) [41,42]. Thus, a compound which unbinds from the channel with a long time constant (e.g.…”
Section: Targets and Mechanisms In Drug-induced Arrhythmiamentioning
confidence: 99%